As conseqüências das transformações organizacionais pós-90 e o novo perfil do trabalhador : um estudo de caso - Treff, Marcelo A. (2007)
The aim of this thesis is to analyze, through a case-study in a large company of paper and cellulose, the consequences for a worker imposed by the process of productive restructure, during the 1990s, after the commercial opening, marked by the changes in the productive and organizational structures. The subjects of this research were workers and ex-workers, as well as managers and ex-managers. The collected data was done through semi-structured questions, documental sources and non-systematic observation of the workers daily routines. The analysis of the data prioritized the qualitative understanding of the reality presented according to theoretical references and revealed a strong increase in the level of demands to the worker, besides the acquisition of new skills in a context determined by the decrease of jobs and by the increase of the informality, in addition to a preoccupying picture in relation to educational possibilities connected to this reality